Initial experience with pulsed field ablation for atrial fibrillation - Magni, Federico T.; Mulder, Bart A.; Groenveld, Hessel F.; Wiesfeld, Ans C. P.; Tieleman, Robert G.; Cox, Moniek G.; Van Gelder, Isabelle C.; Smilde, Tom; Tan, Eng S.; Rienstra, Michiel; Blaauw, Yuri (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Pulsed field ablation (PFA) was recently introduced for treatment of symptomatic atrial fibrillation (AF) with the claim of selectively ablating the myocardium whilst sparing surrounding tissues. We present our initial experience with a PFA catheter for pulmonary vein isolation (PVI) and describe procedural findings and peri-procedural safety of the first 100 patients. Methods: We investigated 100 patients treated for symptomatic AF using the FARAWAVE PFA catheter (Farapulse, Menlo Park, California) between July 2021 and March 2022. Procedure workflow and electrophysiological findings at the time of ablation, peri-procedural complications, and operator learning curves are described. Results: Mean age of patients was 62.9±9.4 years, 62% were male and 80% had paroxysmal AF. Median CHA₂DS₂-VASc score was 1.5 (IQR: 1.0-2.0) and mean left atrial volume index was 35.7±9.6ml/m2. In 88 (88%) patients PVI alone was performed and in 12 (12%) additional ablation of the posterior wall was performed. 3D-electroanatomic mapping was performed in 18 (18%) patients. Procedures without mapping lasted 52.3±16.6min. Mean number of applications per pulmonary vein (PV) were 8.1±0.6. In all patients (100%) all PVs were confirmed to be isolated. The learning curves of the two operator who performed > 20 procedures showed negligible variation of performance over time and practice did not significantly predict procedure time (Operator 1 (senior): R2=0.034, p=0.35; Operator 2 (junior): R2=0.004, p=0.73). There was no difference between the procedure times between senior and junior operator (Operator 1: 46.9±9.7 min vs. Operator 2: 45.9±9.9 min; p=0.73). The only complications observed were two cases of bleeding at the site of percutaneous access. Conclusions: Our initial experience shows that use of the PFA catheter for pulmonary vein isolation (PVI) is safe, fast, and easy-to-learn.